Implementing the Contextual Teaching and Learning to Improve Students' Mathematical Connection and Representation Skills - Adrina Lony (International Journal of Educational Development and Innovation, 2021)
This study aims to improve students' mathematical connection and representation skills as well as students' learning activities. This study implemented the Contextual Teaching and Learning (CTL) for students in studying the topic of linear programming. The subjects were 36 students of eleventh grade at MAN Binjai consisting of 13 male and 19 female students. The purpose of the observations was to measure students' learning activities and using the tests to measure students' mathematical connection and representation skills, and also questionnaires to measure students' positive responses in learning mathematics. The results showed that there was an increase in students' mathematical connection skills with the mean percentage of 65.63% for Cycle 1 and 87.50% for Cycle 2. There was an increase in students' mathematical representation skills with the mean percentage of 75% for Cycle 1 and 93.75% for Cycle 2, and there was an increase in students' learning activities with the mean percentage of 80.72% for Cycle 1 and 87.86% for Cycle 2. Students who were taught with the aid of CTL approach could increase their learning activities in the good category.